Consulta de enfermagem à criança com perda de integridade cutânea no pós-alta hospitalar - Matos, Ayana Carolina Gonçalves Teixeira (2017)
A qualitative study based on the methodology of action research, with the general objective of implant the nursing consultation to the child with loss of skin integrity after hospital discharge, and specific to identify human needs for post-discharge hospital care in children with loss of cutaneous integrity and in their relative / caregiver; To know the difficulties of family members / caregivers or the maintenance of care for child with loss of cutaneous integrity after hospital discharge and to draw up individualized therapeutic plans for children with loss of cutaneous integrity in the post-hospital hospital and their relatives / caregivers to ensure continuity of care. Developed between 2016 and 2017, after approval by the Committee of Ethics and Research under Opinion number 1,701,659 and CAAE: 57534516.7.0000.0053. Four nurses, 10 children with loss of cutaneous integrity in hospital post-discharge and their relatives / caregivers, who before the collection knew the objectives, risks, benefits of study research, and the relatives / caregivers signed the terms of free consent And enlightened and the lesser, the term of free and informed assent. For the production of the data a semi-structured interview, structured observation and field diary were used, after which they were submitted to content analysis. Results of this study are organized in three articles: the first, entitled Perception of family members / caregivers about caring for children with loss of cutaneous integrity, aimed at knowing the need to know the challenges of family members / caregivers for the maintenance of child care with ICP As results, the relatives / caregivers of the child with loss of skin integrity received guidelines for home care at discharge, experienced feelings of relief, withdrawal from hospitalization, and fear and insecurity in causing harm to the child , Thus seeking help in the services and in the neighborhood, overprotecting the child, avoiding harm and readmission, and faced the lack of resources to care for; The second entitled Nursing care for children with loss of cutaneous integrity during action research, had as objectives to describe nursing problems and diagnoses identified in the child with loss of cutaneous integrity in hospital post-discharge and his relative / caregiver, and to discuss difficulties of the Nurses in the implementation of care systematization and showed that the nursing problems of the child and his relative / caregiver reflected directly on the care offered to the child and for this reason they needed interventions in order to guarantee survival of this child and to minimize possibilities of re-hospitalizations. The nurses evidenced the lack of time, overload, inadequate quantification of professionals as difficulties to implant the SAE, yet they were able to identify a range of problems and nursing diagnoses that gave visibility to their work process and ratified the need for SAE implantation; The third, entitled Human needs of children with loss of skin integrity and their relatives: Maslow's theory, aimed at identifying human needs of children with loss of cutaneous integrity and their relatives / caregivers after hospital discharge, in this the results highlighted the emergency Hierarchical and multifaceted needs that demand the search for resilience, self-valorization and valuation to promote self-esteem, autonomy and maintenance of the necessary care for the restoration of cutaneous integrity that allow the family to recover the harmonious everyday dynamics; To the relatives / caregivers possibilities to relive dreams of self-realization distanced from negative feelings and that stimulate their longings to the realization and socialization of the child. This study reached the implantation of the systematization of nursing care in its historical stages, and nursing diagnoses, during this process the familiar / caregiver challenges to the maintenance of the care of children with ICP after hospital discharge and the Difficulties in ensuring systematization. The findings justify the need to strengthen care centered on the child and his / her family, in preparation for hospital discharge to ensure continuity of care at home. And the process implemented needs to move to the other stages, planning, implementing care and evaluating it